2019
DOI: 10.1038/s41598-019-45411-9
|View full text |Cite
|
Sign up to set email alerts
|

ZNF518B gene up-regulation promotes dissemination of tumour cells and is governed by epigenetic mechanisms in colorectal cancer

Abstract: Most of colorectal cancer CRC-related death is due to metastasis and the finding of markers for prognosis of invasiveness, constitutes an appealing challenge. Here, after analysing cDNA array containing 43 tumour and 5 normal mucosa samples, we report that the expression of the ZNF518B gene as a whole and that of its two major splicing isoforms are significantly increased in tumours. The canonical isoform was also up-regulated in a patients’ cohort containing 70 tumour and 69 adjacent ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 28 publications
(44 reference statements)
5
23
0
Order By: Relevance
“…Thus, we expect that nuCpos is applicable to prediction-based engineering and more effective for synthesizing functional elements. Similarly, nuCpos can also be used to examine whether DNA sequences of interest are suitable for nucleosome formation, as previously done with NuPoP [46, 47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we expect that nuCpos is applicable to prediction-based engineering and more effective for synthesizing functional elements. Similarly, nuCpos can also be used to examine whether DNA sequences of interest are suitable for nucleosome formation, as previously done with NuPoP [46, 47].…”
Section: Discussionmentioning
confidence: 99%
“…These nucleosomes are suitable for in silico reproduction of in vivo observations. Importantly, for the currently available bioinformatics method NuPoP, the reliability of locus-level nucleosome prediction has seldom been demonstrated, despite its wide use in previous studies [3847].…”
Section: Introductionmentioning
confidence: 99%
“…Western blot analyses. Western blot analyses were carried out essentially as previously described 40 . Briefly, cultured cells were extracted with RIPA buffer (50 mM Tris-HCl pH 7.5, 150 mM NaCl, 1% Triton X-100, 0.1% SDS, 0.5% deoxycholic acid sodium salt (w/v)) supplemented with 2 μl/ml protease inhibitor cocktail (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…As the dysregulation of this enzyme has been associated with CRC [ 8 ], we further developed the initial work with CRC cell lines [ 1 ] and showed that ZNF518B is up-regulated in patients of colorectal cancer. By silencing the gene in CRC cell lines, it was demonstrated that its expression favours cell migration, invasiveness and other phenotypic variations, which suggests that the gene may be involved in the epithelial-to-mesenchymal transition (EMT) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%